Methylphenidate Treatment of Cognitive Dysfunction in Adults After Mild to Moderate Traumatic Brain Injury: Rationale, Efficacy, and Neural Mechanisms - Levin, Harvey; Troyanskaya, Maya; Petrie, JoAnn; Wilde, Elisabeth A.; Hunter, Jill V.; Abildskov, Tracy J.; Scheibel, Randall S. (Frontiers in Neurology, 2019)
Abstract Positive effects of methylphenidate (MPH) on attention and cognitive processing speed have been reported in studies of patients with moderate to severe traumatic brain injury (TBI). Studies which have acquired functional brain imaging before and while using MPH have also found alteration of brain activation while performing a cognitive task; in some studies, this alteration of activation in selective brain regions was also related to improved performance on cognitive tests administered outside of the scanning environment. Enhanced cognitive performance has been reported after single doses of MPH and after daily treatment over durations of up to and exceeding one month. Preclinical research and both positron emission tomography and single photon emission tomography of humans have shown that MPH increases extracellular dopamine and norepinephrine; the dose effects of MPH have an inverted U-shaped function where high doses may cause insomnia, nervousness, and increased heart rate among other symptoms and impair cognitive performance, whereas too low a dose fails to improve cognitive performance. In the past five years, small clinical trials and experimental pilot studies have found therapeutic effects of single and repeated low doses of MPH in patients with mild TBI who reported cognitive dysfunction. This literature also suggests that MPH may interact with concurrent cognitive interventions to enhance their effects. This focused review will critically evaluate the recent literature on MPH effects on cognitive dysfunction after mild to moderate TBI. To elucidate the neural mechanisms of MPH effects, this review will also include recent imaging research, preclinical, and experimental human studies.